The value of safety or the value of the good? - Linda Andersson Järnberg; Daniela Andrén; Maria Bratt Börjesson; Lars Hultkrantz; Eva Elisabet Rutström; Elin Vimefall (Örebro University School of Business, 2024)
This study analyzes how the willingness to pay (WTP) for a risk reduction for traffic accidents varies depending on the specific traffic safety measures and whether they are framed as public or private goods. Building on previous studies, we designed and conducted a contingent valuation survey targeting a representative sample of the Swedish population, assessing WTP for eight different measures aimed at increasing the safety of vulnerable road users. Our findings reveal that while keeping the risk reduction constant, WTP is higher for well-established traffic safety measures, such as anti-slip treatments and improved lighting. Conversely, new technologies, like mobile apps and sensors, elicit lower WTP. However, respondents express a higher WTP when these technological measures are provided as a public good. These results suggest that acceptance and perceived reliability of the measures significantly influence WTP. The findings have important implications for cost-benefit analyses and evidence-based policymaking in transportation safety, particularly regarding the implementation of new technology in road safety infrastructure.
Keywords: D12; H41; R41; 330; traffic safety; willingness to pay; public good; private good; infrastructure; bicyclists and pedestrians; interval regression